The Palgrave Handbook of Kenyan History
XVI, 265 p. 1 illus. in color.
Keywords: This volume covers Kenya’s history, society, culture, economics, politics, and environment from precolonial times through the first years of independence. The book comprises twenty-one chapters divided into two parts. Part I focuses on the long precolonial moment, detailing the nature of precolonial Kenyan societies and their economics, politics, gender dynamics, and social organization. Part II examines Kenyan societies’ encounters with British colonialism, critically outlining the impact and implications of these encounters. The volume concludes with an examination of political consolidation after the country’s attainment of political independence and the subsequent foundations for political authoritarianism. Wanjala S. Nasong’o is Professor of International Studies at Rhodes College in Memphis, USA. Maurice N. Amutabi is Professor and Director of the Center for Science and Technology Studies at the Technical University of Kenya. Toyin Falola is Professor of History, University Distinguished Teaching Professor, and the Jacob and Frances Sanger Mossiker Chair in the Humanities at the University of Texas at Austin, USA. He is an honorary professor at the University of Cape Town, South Africa, and Extraordinary Professor of Human Rights at the University of the Free State, South Africa. .